Social consciousness of Mahua campus writings in the 1980s and their development - Pong, Siew Choo (2017)
The research is to study the formation, development and the continuation as well as deviation of 1980s Mahua Campus Writings regarding the Chinese community itself and the country as a whole. The time frame of this study falls within 22 years governance (i.e. from 1981 to 2003) by the fourth Prime Minister Tun Dr. Mahathir Mohamad. The style of Dr. Mahathir’s governance, normally named as Mahathirism by social science scholar, and its implementation of certain political, economic, culture and education policy had brought a tremendous impact to the Chinese community and the Chinese campus students in the time mentioned. The students express themselves and their opinions on the incidents that occurred in the leadership of Mahathir during and after their graduation. However, studies show that social awareness in their writings not as high as assumed, but it is more prone to emotional expression in writing. After graduation, some of them have set aside their writings, some still find writing inspiration, some geared up in the ivory tower as academic staff and some have involved in business meanwhile trying to encourage the youngster involved in writing. The real fact is these groups show less inspiration in writing and attention to social, society and the state issues as well. This proves that some scholars mention that Mahua Literature as a whole is still at its youth stage of development.